1978
DOI: 10.1107/s0567740878006159
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structures of trimesic acid, its hydrates and complexes. IV. Trimesic acid–dimethyl sulphoxide

Abstract: C9H6Os. C2HsSO iS monoclinic, with a = 8.743 (4), b = 6.803 (4), c = 10-677 (5) A, fl = 96.24 (4) °, z = 2, space group P2~ or P2~/m. The structure was refined to R = 8.4% (in space group P2 0 for 1751 counter reflections. There are hydrogen bonds both between pairs of TMA molecules (but carboxylic acid dimers are not formed) and between TMA and DMSO molecules. O atoms of the DMSO molecules are part of the walls of channels formed by the TMA molecules, while the methyl groups of the DMSO molecules lie within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…However, TMA was recently revisited from a fresh perspective, after CSP calculations revealed an energetically stable, low-density polymorphic form, referred to as the δ-polymorph, which remained hidden, despite many groups studying the crystallization behavior of this molecule over the last 50 years. [285][286][287][288][289][290][291][292][293][294] In this study, a high throughput crystallization workflow was developed to screen 280 binary solvent crystallization conditions, of which less than 2% either yielded this δ-polymorph directly, or gave a structure that transformed to this form after activation of the crystal pores. [295] Unlike the nonporous α-polymorph reported by Duchamp et al, the computationally-identified δpolymorph of TMA had a SA BET 910 m 2 g -1 at 77.3 K. CSP was also used by Hisaki et al (Tp-apo, Figures 13 and 16) [296] to predict the structure of a carboxylic acid-based HOF material, that could not be determined directly from X-ray data alone.…”
Section: Tuning Crystal Porosity By Controlling Molecular Packingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, TMA was recently revisited from a fresh perspective, after CSP calculations revealed an energetically stable, low-density polymorphic form, referred to as the δ-polymorph, which remained hidden, despite many groups studying the crystallization behavior of this molecule over the last 50 years. [285][286][287][288][289][290][291][292][293][294] In this study, a high throughput crystallization workflow was developed to screen 280 binary solvent crystallization conditions, of which less than 2% either yielded this δ-polymorph directly, or gave a structure that transformed to this form after activation of the crystal pores. [295] Unlike the nonporous α-polymorph reported by Duchamp et al, the computationally-identified δpolymorph of TMA had a SA BET 910 m 2 g -1 at 77.3 K. CSP was also used by Hisaki et al (Tp-apo, Figures 13 and 16) [296] to predict the structure of a carboxylic acid-based HOF material, that could not be determined directly from X-ray data alone.…”
Section: Tuning Crystal Porosity By Controlling Molecular Packingmentioning
confidence: 99%
“…The structure Duchamp reported is nonporous due to the nonplanar hydrogen‐bonded interactions between TMA molecules causing the hydrogen‐bonded networks to interlock. However, TMA was recently revisited from a fresh perspective, after CSP calculations revealed an energetically stable, low‐density polymorphic form, referred to as the δ−polymorph, which remained hidden, despite many groups studying the crystallization behavior of this molecule over the last 50 years 285–294. In this study, a high throughput crystallization workflow was developed to screen 280 binary solvent crystallization conditions, of which less than 2% either yielded this δ‐polymorph directly, or gave a structure that transformed to this form after activation of the crystal pores 295.…”
Section: Tuning the Properties Of Porous Molecular Materialsmentioning
confidence: 99%
“…For the first report on the title solvate structure, see: Herbstein et al (1978). For the use of trimesic acid as a building block for supramolecular networks, see: Almeida Paz & Klinowski (2004).…”
Section: Related Literaturementioning
confidence: 99%
“…The clathration ability of TMA allowed to prepare a number of solvate structures, including hydrates, and consequently determination of these structures. Among them, the dimethylsulfoxide (DMSO) solvate has been reported already 30 years ago (Herbstein et al, 1978). The data were collected at room temperature with Mo-Kα radiation.…”
Section: S1 Commentmentioning
confidence: 99%
See 1 more Smart Citation